Pharmocracy : Value, Politics, and Knowledge in Global Biomedicine - Sunder Rajan, Kaushik, 1974- (Book collections on Project MUSE., 2017)
Kaushik Sunder Rajan traces the structure and operation of what he calls pharmocracy-a concept explaining the global hegemony of the multinational pharmaceutical industry. He outlines pharmocracy's logic in two case studies from contemporary India to demonstrate the stakes of its intersection with health, politics, democracy, and global capital.